Casting the native subject: Ethnographic practice and the (re)production of diﬀerence (Casting the Other)
In the 1980s, the recognition that organizations are cultural entities requiring cultural analysis transformed the study of management and organizations.2Relying on the lens of culture meant eschewing large-scale surveys and laboratory experiments in favour of in-depth researcher immersion in local ﬁeldsites conducted under the label of ethnography. Ethnography’s main epistemological claim is an endogenic or ‘insider’ one – that it oﬀers an understanding of ‘natives’ in their own cultures. Within the wider anthropological tradition in which ethnography is rooted, the term itself denotes the practice of writing (graphy) about cultures (ethno), typically about ‘other’ and ‘native’ cultures (Axtell 1981; Vidich and Lyman 1994). Within the Anglo-American and French traditions, ethnography is often used to refer to the actual ﬁeldwork that yields ‘ethnological’ insights, though both terms (ethnography and ethnology) are sometimes used interchangeably. Often referred to as an emic (as opposed to etic) tradition, conventional ethnography does not merely imply intense researcher involvement in the ﬁeld, but is committed to understanding and presenting the natives from an ‘inside’ point of view (Gregory 1983; Schwartzman 1993).